Guidance supporting Europe's aspiring entrepreneurs : policy and practice to harness future potential - (:unkn) unknown (Publications Office of the European Union, 2011)
"The European Commission and Member States have been working together since the 1990s to develop an entrepreneurial education and training agenda in Europe. Yet to date there had been no study on how guidance can encourage entrepreneurship and the cultivation of an entrepreneurial mindset. This Cedefop study aims at better understanding how guidance can support entrepreneurship learning and contributes to the development of career management skills for entrepreneurs. The aims of the study are: to illustrate and assess the role of guidance in supporting entrepreneurship learning in initial vocational education and training (IVET) and higher education (HE); to examine what kind of guidance is available for enterprise start ups for IVET and HE students; analyse what kind of guidance is available to develop the career management skills of aspiring and novice entrepreneurs. The study covers the European Union (EU) countries, plus Iceland, Liechtenstein and Norway." (Hrsg., BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; G 1.2.3.2 Anforderungen & Bedarfe; I 2.2 Europa; Unternehmertum; Berufliche Selbständigkeit; Unternehmerische Qualifikation; Berufsberatung; Laufbahnberatung; Berufsausbildung; Hochschulbildung; Europäische Union